The Effectiveness of an Integrative Coaching Psychology Intervention Program on the Well-Being of Parent with Preadolescent with Symptoms of Externalizing Disorders - Pahlavnejad, Amir Mohammad; Ghanbaripanah, Afsaneh; Nourmohammadi, Farahnaz; Poushaneh, Kambiz (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: The objective of this study was to evaluate the effectiveness of an integrative coaching psychology intervention program on the well-being of parent with preadolescent with symptoms of externalizing disorders. Methods and Materials: This quasi-experimental study utilized a mixed between-within subjects design, including one experimental group and one control group, with random assignment and pre-test, post-test, and two-month follow-up assessments. The participants were parents of preadolescent diagnosed with symptoms of externalizing disorders, selected through purposive sampling. The intervention involved a 10-week integrative coaching psychology program. Data were collected using the PERMA well-being questionnaire and the Achenbach Child Behavior Checklist (CBCL). Data analysis included descriptive statistics and two-way repeated measures ANOVA to evaluate the impact of the intervention. Findings: The results indicated a significant improvement in the well-being scores of the experimental group from pre-test to post-test and follow-up stages (p < .01), with no significant difference between post-test and follow-up scores, indicating the stability of the intervention’s effects. The experimental group also showed significantly lower scores in negative emotions and loneliness, and higher scores in overall happiness, health, and well-being compared to the control group. The control group did not exhibit significant changes across the stages. Conclusion: The integrative coaching psychology intervention program was effective in enhancing the well-being of parent with preadolescent with symptoms of externalizing disorders. The program led to significant improvements in positive emotions, engagement, relationships, meaning, and accomplishment, while reducing negative emotions and loneliness.